2021
DOI: 10.1186/s13567-021-00978-y
|View full text |Cite
|
Sign up to set email alerts
|

A detailed analysis of innate and adaptive immune responsiveness upon infection with Salmonella enterica serotype Enteritidis in young broiler chickens

Abstract: Salmonella enterica serotype Enteritidis (SE) is a zoonotic pathogen which causes foodborne diseases in humans as well as severe disease symptoms in young chickens. More insight in innate and adaptive immune responses of chickens to SE infection is needed to understand elimination of SE. Seven-day-old broiler chickens were experimentally challenged with SE and numbers and responsiveness of innate and adaptive immune cells as well as antibody titers were assessed. SE was observed in the ileum and spleen of SE-i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(26 citation statements)
references
References 76 publications
3
23
0
Order By: Relevance
“…Recently, Maekawa et al (2021) also employed a six-color flow cytometric assay to compare the dynamic changes of CD107 + CTLs, NK cells, and regulatory T cells (Tregs) in the larynx-trachea of chickens immunized with different ILTV vaccines after challenge and found that the cellular immune responses elicited by different ILTV vaccines varied in the upper respiratory tract after challenge, and that activated CTLs rather than NK cells play a main role in vaccine protection. In addition, combining multi-color flow cytometry and gene expression profiling, macrophages and distinct DCs in chickens were characterized and shown to be activated based on upregulated expression of MHC II and costimulatory molecules CD40 and CD80 in the setting of infection ( Vu Manh et al, 2014 ; Meijerink et al, 2021 ). These studies highlighted the importance to analyze cellular immunity to avian viral infections by flow cytometry.…”
Section: Flow Cytometric Analysis Of Different Cellular Subsetsmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, Maekawa et al (2021) also employed a six-color flow cytometric assay to compare the dynamic changes of CD107 + CTLs, NK cells, and regulatory T cells (Tregs) in the larynx-trachea of chickens immunized with different ILTV vaccines after challenge and found that the cellular immune responses elicited by different ILTV vaccines varied in the upper respiratory tract after challenge, and that activated CTLs rather than NK cells play a main role in vaccine protection. In addition, combining multi-color flow cytometry and gene expression profiling, macrophages and distinct DCs in chickens were characterized and shown to be activated based on upregulated expression of MHC II and costimulatory molecules CD40 and CD80 in the setting of infection ( Vu Manh et al, 2014 ; Meijerink et al, 2021 ). These studies highlighted the importance to analyze cellular immunity to avian viral infections by flow cytometry.…”
Section: Flow Cytometric Analysis Of Different Cellular Subsetsmentioning
confidence: 99%
“…Classical methods for measuring T cell proliferation include 3 H-Thymidine ( 3 H-TdR) incorporation assays ( Maurer, 1981 ) and MTT assay ( Mosmann, 1983 ) but have disadvantages of generating radioactive waste and lacking of sensitivity, respectively. Therefore, new methods such as CFSE (carboxyfluorescein diacetate succinimidyl ester) and CellTrace Violet (CTV) labelling, BrdU (5'-Bromo-2'-deoxyuridine) and EdU (ethynyl-deoxyuridine) incorporation assays ( Motobu et al, 2002 ; Dalgaard et al, 2010 ; Alvarez et al, 2020 ; Meijerink et al, 2021 ) that are more sensitive and environment-friendly have been introduced for T cell proliferation assay. These methods can be combined with flow cytometry to identify the phenotype of immune cells at the same time and have been validated in chickens ( Table 2 ).…”
Section: Detection Of T Cell Proliferationmentioning
confidence: 99%
See 2 more Smart Citations
“…Recently, [35] described the changes in the innate and adaptive immune system that are generated in birds after infection with S. Enteritidis in detail. As in the control group of our study, one week after the challenge with Salmonella, there was an increase in the proportion of CD8+ T lymphocytes and other cells, but this, according to these authors, is not sufficient to prevent the progressive colonization of the cecum and spleen with Salmonella.…”
Section: Discussionmentioning
confidence: 99%